Minimum Quality Regulations and the Demand for Child Care Labor - Umair Ali; Chris M. Herbst; Christos A. Makridis (Institute of Labor Economics (IZA), 2021)
Minimum quality regulations are often justified in the child care market because of the presence of information frictions between parents and providers. However, regulations can also have unintended consequences for the quantity and quality of services provided. In this paper, we merge new data on states' child care regulations for maximum classroom group sizes and child-to-staff ratios with the universe of online job postings to study the impact of regulations on the demand for and characteristics of child care labor. Our identification strategy exploits the unprecedented variation in regulatory reform during the COVID-19 pandemic, relying on changes both within states over time and across children's age groups. We find robust evidence that these regulations reduce the number of child care job postings and encourage providers to substitute away from higher-skilled postings, thereby increasing the number of positions that are out-of-compliance with state law. Furthermore, we show that regulations adversely affect mothers' labor force participation. In sum, the results imply that child care regulations may reduce the demand for child care labor, while simultaneously altering the composition of the workforce.
Keywords: H75; J21; I28; 330; child care; COVID-19; employment; state regulation; women